Laser applications in surgery - Azadgoli, Beina; Baker, Regina Y. (Annals of Translational Medicine; Vol 4, No 23 (December 19, 2016): Annals of Translational Medicine (Focus on: “Innovations & Technology in Surgery”), 2016)
In modern medicine, lasers are increasingly utilized for treatment of a variety of pathologies as interest in less invasive treatment modalities intensifies. The physics behind lasers allows the same basic principles to be applied to a multitude of tissue types using slight modifications of the system. Multiple laser systems have been studied within each field of medicine. The term “laser” was combined with “surgery,” “ablation,” “lithotripsy,” “cancer treatment,” “tumor ablation,” “dermatology,” “skin rejuvenation,” “lipolysis,” “cardiology,” “atrial fibrillation (AF),” and “epilepsy” during separate searches in the PubMed database. Original articles that studied the application of laser energy for these conditions were reviewed and included. A review of laser therapy is presented. Laser energy can be safely and effectively used for lithotripsy, for the treatment of various types of cancer, for a multitude of cosmetic and reconstructive procedures, and for the ablation of abnormal conductive pathways. For each of these conditions, management with lasers is comparable to, and potentially superior to, management with more traditional methods.